Redesigning the Clinical Effectiveness Research Paradigm: Innovation and Practice-Based Approaches: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Recent scientific and technological advances have accelerated our understanding of the causes of disease development and progression, and resulted in innovative treatments and therapies. Ongoing work to elucidate the effects of individual genetic variation on patient outcomes suggests the rapid pace of discovery in the biomedical sciences will only accelerate. However, these advances belie an important and increasing shortfall between the expansion in therapy and treatment options and knowledge about how these interventions might be applied appropriately to individual patients. The impressive gains made in Americans' health over the past decades provide only a preview of what might be possible when data on treatment effects and patient outcomes are systematically captured and used to evaluate their effectiveness. Needed for progress are advances as dramatic as those experienced in biomedicine in our approach to assessing clinical effectiveness. In the emerging era of tailored treatments and rapidly evolving practice, ensuring the translation of scientific discovery into improved health outcomes requires a new approach to clinical evaluation. A paradigm that supports a continual learning process about what works best for individual patients will not only take advantage of the rigor of trials, but also incorporate other methods that might bring insights relevant to clinical care and endeavor to match the right method to the question at hand. The Institute of Medicine Roundtable on Value & Science-Driven Health Care's vision for a learning healthcare system, in which evidence is applied and generated as a natural course of care, is premised on the development of a research capacity that is structured to provide timely and accurate evidence relevant to the clinical decisions faced by patients and providers. As part of the Roundtable's Learning Healthcare System series of workshops, clinical researchers, academics, and policy makers gathered for the workshop Redesigning the Clinical Effectiveness Research Paradigm: Innovation and Practice-Based Approaches. Participants explored cutting-edge research designs and methods and discussed strategies for development of a research paradigm to better accommodate the diverse array of emerging data resources, study designs, tools, and techniques. Presentations and discussions are summarized in this volume.
Keywords: Health and Medicine

A National Cancer Clinical Trials System for the 21st Century: Reinvigorating the NCI Cooperative Group Program - Institute of Medicine (The National Academies Press, 2010)
The National Cancer Institute's (NCI) Clinical Trials Cooperative Group Program has played a key role in developing new and improved cancer therapies. However, the program is falling short of its potential, and the IOM recommends changes that aim to transform the Cooperative Group Program into a dynamic system that efficiently responds to emerging scientific knowledge; involves broad cooperation of stakeholders; and leverages evolving technologies to provide high-quality, practice-changing research.
Keywords: Health and Medicine

A Population-Based Policy and Systems Change Approach to Prevent and Control Hypertension - Institute of Medicine (The National Academies Press, 2010)
Hypertension is one of the leading causes of death in the United States, affecting nearly one in three Americans. It is prevalent in adults and endemic in the older adult population. Hypertension is a major contributor to cardiovascular morbidity and disability. Although there is a simple test to diagnose hypertension and relatively inexpensive drugs to treat it, the disease is often undiagnosed and uncontrolled. A Population-Based Policy and Systems Change Approach to the Prevention and Control Hypertension identifies a small set of high-priority areas in which public health officials can focus their efforts to accelerate progress in hypertension reduction and control. It offers several recommendations that embody a population-based approach grounded in the principles of measurement, system change, and accountability. The recommendations are designed to shift current hypertension reduction strategies from an individual-based approach to a population-based approach. They are also designed to improve the quality of care provided to individuals with hypertension and to strengthen the Center for Disease Control and Prevention's leadership in seeking a reduction in the sodium intake in the American diet to meet dietary guidelines. The book is an important resource for federal public health officials and organizations, especially the Center for Disease Control and Prevention, as well as medical professionals and community health workers.
Keywords: Health and Medicine

Preliminary Observations on Information Technology Needs and Priorities at the Centers for Medicare and Medicaid Services: An Interim Report - National Research Council (The National Academies Press, 2010)
Increasingly, the core mission of the Centers for Medicare and Medicaid Services (CMS), an agency of the Department of Health and Human Services, is expanding from one of focusing on prompt claims payment to one of becoming more broadly involved in improving health care quality and efficiency. The requirements for the information technology (IT) systems of CMS are changing as its mission changes, and the efforts to evolve its systems from those designed to support the agency's historical mission come in the midst of a push to modernize the nation's health care IT more broadly. These new challenges arise even as CMS must meet challenging day-to-day operational requirements and make frequent adjustments to its business processes, code, databases, and systems in response to changing statutory, regulatory, and policy requirements. In light of these and other emerging challenges, CMS asked the National Research Council to conduct a study that would lay out a forward-looking vision for the Centers for Medicare and Medicaid Services, taking account of CMS's mission, business processes, and information technology requirements. The study is being conducted in two phases. The first, resulting in the present volume, draws on a series of teleconferences, briefings, and an information-gathering workshop held in Washington, D.C., on September 27-28, 2010. The second phase, drawing on that workshop and on additional briefings, site visits, and committee deliberations, will result in a final report with recommendations, to be issued at the end of the project in 2011.
Keywords: Health and Medicine

Steps Toward Large-Scale Data Integration in the Sciences: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
Steps Toward Large-Scale Data Integration in the Sciences summarizes a National Research Council (NRC) workshop to identify some of the major challenges that hinder large-scale data integration in the sciences and some of the technologies that could lead to solutions. The workshop was held August 19-20, 2009, in Washington, D.C. The workshop examined a collection of scientific research domains, with application experts explaining the issues in their disciplines and current best practices. This approach allowed the participants to gain insights about both commonalities and differences in the data integration challenges facing the various communities. In addition to hearing from research domain experts, the workshop also featured experts working on the cutting edge of techniques for handling data integration problems. This provided participants with insights on the current state of the art. The goals were to identify areas in which the emerging needs of research communities are not being addressed and to point to opportunities for addressing these needs through closer engagement between the affected communities and cutting-edge computer science.
Keywords: Health and Medicine

The Role of Human Factors in Home Health Care: Workshop Summary - National Research Council (The National Academies Press, 2010)
The rapid growth of home health care has raised many unsolved issues and will have consequences that are far too broad for any one group to analyze in their entirety. Yet a major influence on the safety, quality, and effectiveness of home health care will be the set of issues encompassed by the field of human factors research—the discipline of applying what is known about human capabilities and limitations to the design of products, processes, systems, and work environments. To address these challenges, the National Research Council began a multidisciplinary study to examine a diverse range of behavioral and human factors issues resulting from the increasing migration of medical devices, technologies, and care practices into the home. Its goal is to lay the groundwork for a thorough integration of human factors research with the design and implementation of home health care devices, technologies, and practices. On October 1 and 2, 2009, a group of human factors and other experts met to consider a diverse range of behavioral and human factors issues associated with the increasing migration of medical devices, technologies, and care practices into the home. This book is a summary of that workshop, representing the culmination of the first phase of the study.
Keywords: Health and Medicine; Behavioral and Social Sciences

Assessing the Effects of the Gulf of Mexico Oil Spill on Human Health: A Summary of the June 2010 Workshop - Institute of Medicine (The National Academies Press, 2010)
From the origin of the leak, to the amount of oil released into the environment, to the spill's duration, the 2010 Gulf of Mexico oil spill poses unique challenges to human health. The risks associated with extensive, prolonged use of dispersants, with oil fumes, and with particulate matter from controlled burns are also uncertain. There have been concerns about the extent to which hazards, such as physical and chemical exposures and social and economic disruptions, will impact the overall health of people who live and work near the area of the oil spill. Although studies of previous oil spills provide some basis for identifying and mitigating the human health effects of these exposures, the existing data are insufficient to fully understand and predict the overall impact of hazards from the Deepwater Horizon oil spill on the health of workers, volunteers, residents, visitors, and special populations. Assessing the Effects of the Gulf of Mexico Oil Spill on Human Health identifies populations at increased risks for adverse health effects and explores effective communication strategies to convey health information to these at-risk populations. The book also discusses the need for appropriate surveillance systems to monitor the spill's potential short- and long-term health effects on affected communities and individuals. Assessing the Effects of the Gulf of Mexico Oil Spill on Human Health is a useful resource that can help policy makers, public health officials, academics, community advocates, scientists, and members of the public collaborate to create a monitoring and surveillance system that results in "actionable" information and that identifies emerging health risks in specific populations.
Keywords: Health and Medicine; Environment and Environmental Studies

Perspectives from United Kingdom and United States Policy Makers on Obesity Prevention: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Both the United Kingdom and the United States are grappling with nationwide epidemics of obesity. Obesity contributes to diabetes, cardiovascular disease, and some cancers, among other diseases. Although many people are aware of obesity's causes and consequences, few see it as a problem for their own families--despite clinical evidence to the contrary. Given this disconnect between perception and reality, policy makers in both countries struggle to find a way to reach people to encourage change. The IOM brought together policy makers from the U.K. and U.S. for a workshop on October 22, 2009, to discuss the challenges of and promising approaches to the struggle against obesity. Presenters spoke about current policies, programs, and partnerships that are addressing the obesity epidemic and evidence for effective strategies to change perception and behaviors. The workshop, summarized in this document, provided an opportunity for both countries to learn from each other's efforts and to consider how to apply new strategies at home.
Keywords: Food and Nutrition; Health and Medicine

Provision of Mental Health Counseling Services Under TRICARE - Institute of Medicine (The National Academies Press, 2010)
In this book, the IOM makes recommendations for permitting independent practice for mental health counselors treating patients within TRICARE--the DOD's health care benefits program. This would change current policy, which requires all counselors to practice under a physician's supervision without regard to their education, training, licensure or experience.
Keywords: Health and Medicine

Cardiovascular Disability: Updating the Social Security Listings - Institute of Medicine (The National Academies Press, 2010)
The Social Security Administration (SSA) uses a screening tool called the Listing of Impairments to identify claimants who are so severely impaired that they cannot work at all and thus immediately qualify for benefits. In this report, the IOM makes several recommendations for improving SSA's capacity to determine disability benefits more quickly and efficiently using the Listings.
Keywords: Health and Medicine

Evaluation of Biomarkers and Surrogate Endpoints in Chronic Disease - Institute of Medicine (The National Academies Press, 2010)
Many people naturally assume that the claims made for foods and nutritional supplements have the same degree of scientific grounding as those for medication, but that is not always the case. The IOM recommends that the FDA adopt a consistent scientific framework for biomarker evaluation in order to achieve a rigorous and transparent process.
Keywords: Health and Medicine

Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Reducing the Treatment Gap, Improving Quality of Care: Summary of a Joint Workshop by the Institute of Medicine and the Uganda National Academy of Sciences - Institute of Medicine (The National Academies Press, 2010)
Millions of people in sub-Saharan Africa suffer from mental, neurological, and substance use (MNS) disorders, and most do not have the resources to obtain treatment. The Uganda National Academy of Sciences and the Institute of Medicine hosted a workshop to discuss the state of care for MNS disorders in sub-Saharan Africa.
Keywords: Health and Medicine

Value in Health Care: Accounting for Cost, Quality, Safety, Outcomes, and Innovation: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
The United States has the highest per capita spending on health care of any industrialized nation. Yet despite the unprecedented levels of spending, harmful medical errors abound, uncoordinated care continues to frustrate patients and providers, and U.S. healthcare costs continue to increase. The growing ranks of the uninsured, an aging population with a higher prevalence of chronic diseases, and many patients with multiple conditions together constitute more complicating factors in the trend to higher costs of care. A variety of strategies are beginning to be employed throughout the health system to address the central issue of value, with the goal of improving the net ratio of benefits obtained per dollar spent on health care. However, despite the obvious need, no single agreed-upon measure of value or comprehensive, coordinated systemwide approach to assess and improve the value of health care exists. Without this definition and approach, the path to achieving greater value will be characterized by encumbrance rather than progress. To address the issues central to defining, measuring, and improving value in health care, the Institute of Medicine convened a workshop to assemble prominent authorities on healthcare value and leaders of the patient, payer, provider, employer, manufacturer, government, health policy, economics, technology assessment, informatics, health services research, and health professions communities. The workshop, summarized in this volume, facilitated a discussion of stakeholder perspectives on measuring and improving value in health care, identifying the key barriers and outlining the opportunities for next steps.
Keywords: Health and Medicine

Hepatitis and Liver Cancer: A National Strategy for Prevention and Control of Hepatitis B and C - Institute of Medicine (The National Academies Press, 2010)
The global epidemic of hepatitis B and C is a serious public health problem. Hepatitis B and C are the major causes of chronic liver disease and liver cancer in the world. In the next 10 years, 150,000 people in the United States will die from liver disease or liver cancer associated with chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infections. Today, between 800,000 and 1.4 million people in the United States have chronic hepatitis B and between 2.7 and 3.9 million have chronic hepatitis C. People most at risk for hepatitis B and C often are the least likely to have access to medical services. Reducing the rates of illness and death associated with these diseases will require greater awareness and knowledge among health care workers, improved identification of at-risk people, and improved access to medical care. Hepatitis B is a vaccine-preventable disease. Although federal public health officials recommend that all newborns, children, and at-risk adults receive the vaccine, about 46,000 new acute cases of the HBV infection emerge each year, including 1,000 in infants who acquire the infection during birth from their HBV-positive mothers. Unfortunately, there is no vaccine for hepatitis C, which is transmitted by direct exposure to infectious blood. Hepatitis and Liver Cancer identifies missed opportunities related to the prevention and control of HBV and HCV infections. The book presents ways to reduce the numbers of new HBV and HCV infections and the morbidity and mortality related to chronic viral hepatitis. It identifies priorities for research, policy, and action geared toward federal, state, and local public health officials, stakeholder, and advocacy groups and professional organizations.
Keywords: Health and Medicine

Promoting Cardiovascular Health in the Developing World: A Critical Challenge to Achieve Global Health - Institute of Medicine (The National Academies Press, 2010)
Cardiovascular disease (CVD), once thought to be confined primarily to industrialized nations, has emerged as a major health threat in developing countries. Cardiovascular disease now accounts for nearly 30 percent of deaths in low and middle income countries each year, and is accompanied by significant economic repercussions. Yet most governments, global health institutions, and development agencies have largely overlooked CVD as they have invested in health in developing countries. Recognizing the gap between the compelling evidence of the global CVD burden and the investment needed to prevent and control CVD, the National Heart, Lung, and Blood Institute (NHLBI) turned to the IOM for advice on how to catalyze change. In this report, the IOM recommends that the NHLBI, development agencies, nongovernmental organizations, and governments work toward two essential goals: creating environments that promote heart healthy lifestyle choices and help reduce the risk of chronic diseases, and building public health infrastructure and health systems with the capacity to implement programs that will effectively detect and reduce risk and manage CVD. To meet these goals, the IOM recommends several steps, including improving cooperation and collaboration; implementing effective and feasible strategies; and informing efforts through research and health surveillance. Without better efforts to promote cardiovascular health, global health as a whole will be undermined.
Keywords: Health and Medicine

HIV and Disability: Updating the Social Security Listings - Institute of Medicine (The National Academies Press, 2010)
The Social Security Administration (SSA) uses a screening tool called the Listing of Impairments to identify claimants who are so severely impaired that they cannot work at all and thus qualify for disability benefits. In this report, the Institute of Medicine (IOM) makes several recommendations for improving SSA's capacity for determining disability benefits more accurately and quickly using the HIV Infection Listings.
Keywords: Health and Medicine

Returning Home from Iraq and Afghanistan: Preliminary Assessment of Readjustment Needs of Veterans, Service Members, and Their Families - Institute of Medicine (The National Academies Press, 2010)
Nearly 1.9 million U.S. troops have been deployed to Afghanistan and Iraq since October 2001. Many service members and veterans face serious challenges in readjusting to normal life after returning home. This initial book presents findings on the most critical challenges, and lays out the blueprint for the second phase of the study to determine how best to meet the needs of returning troops and their families.
Keywords: Health and Medicine

Considerations for Ensuring Safety and Efficacy of Vaccines and Therapeutic Proteins Manufactured by Using Platform Approaches: Summary of a Workshop - National Research Council (The National Academies Press, 2010)
A major goal of the US Department of Defense (DOD) Transformational Medical Technologies Initiative (TMTI) is to develop countermeasures that will protect military personnel against bioweapons, including specific infectious-disease agents and toxins. An explicit TMTI objective is to respond quickly to such threats by producing an appropriate amount of an effective countermeasure--currently defined as enough material to treat or vaccinate 3 million personnel--within 12 months of identification of a specific threat. DOD officials call for TMTI programs to be up and running by 2014. The National Academies hosted a workshop which brought together scientists from academe, government, and the biotechnology industry to identify and discuss challenges and ideas related to the TMTI's vision of developing countermeasures within a few months after an agent is identified. The workshop focused on manufacturing processes and specifically on the development of "manufacturing platforms"--repeatable components of manufacturing that reduce both development time and risk. An underlying assumption was that demonstrating that integrated platforms can reliably produce safe and efficacious countermeasures might shorten the regulatory approval process. The workshop is summarized in this book.
Keywords: Health and Medicine

Extending the Spectrum of Precompetitive Collaboration in Oncology Research: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Despite spending more time and money in developing novel therapeutics, the success rate for new pharmacologic treatments has been poor. Although the research and development expenditures have grown 13 percent each year since 1970 (a 50-fold increase), the number of new drugs approved annually is no greater now than it was 50 years ago. Over the past decade, skyrocketing costs and the complexity of the scientific knowledge upon which to develop new agents have provided incentives for alternative approaches to drug development, if we are to continue to improve clinical care and reduce mortality. These challenges create opportunities for improved collaboration between industry, academia, government, and philanthropic organizations at each stage in new drug development, marketing, and implementation. Perhaps the most appropriate initial step in addressing the need for collaboration is to consider more precompetitive relationships that allow sharing of scientific information to foster drug development. While these collaborative relationships in basic and preclinical research on drug targets and the early stages of clinical testing are acknowledged to be potentially important drivers for innovation and more rapid marketing of new agents, they also raise a number of concerns that must be addressed. For example, acknowledgment of academic productivity and independence and economic competitiveness must be considered and these challenges managed to foster a culture of collaboration. At the same time, regulatory issues, the need for standardization, and intellectual property concerns must be confronted if the current models for drug development are to be refined to encourage robust participation in precompetitive collaborations. Recognizing the growing importance of precompetitive collaborations in oncology drug development, as well as the challenges these innovative collaborations pose, the National Cancer Policy Forum of the Institute of Medicine held a workshop on February 9 and 10, 2010. This book is a summary of the workshop proceedings.
Keywords: Health and Medicine

Forum on Neuroscience and Nervous System Disorders: 2010 Annual Report - Institute of Medicine (The National Academies Press, 2011)
Keywords: Health and Medicine